Peran Guru Dalam Upaya Meningkatkan Keaktifan Siswa Dengan Menerapkan Metode Tanya Jawab Pada Pembelajaran Online - Jossapat Hendra Prijanto; Firelia de Kock (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2021)
The question and answer method is an effort that can be applied by teachers in learning activities to increase student activity. Student activeness is a problem that is often encounter in learning activities. Learning that is carried out online also has the same problem, namely, students tend to be inactive during learning. Based on the results of observations and teaching practices conducted in grades 7, 8, and 9, it was found that student activity was a problem that often occurred during the online learning process. This was seen from the lack of students responding to teacher messages in the telegram group so that the learning activities seem passive. Through these problems, the purpose of writing this paper is to describe the use of the question and answer method as an effort to increase student activeness in the online learning process. Thus, the role of Christian teachers as facilitators is very necessary to strive for student activeness by using the question and answer method in online learning. The research method was descriptive qualitative. The results of the application of the question and answer method in online learning were quite effective in increasing student activity so that teachers and students have sufficient interaction and communication. To fulfill the role of a Christian teacher as a facilitator, teachers need to equip themselves with pedagogical elements that are in accordance with teacher competency standards.